A study on medical students' level of grittiness - Raymundo, Lorna Catherine G.; Sana, Erlyn A. (2018)
Grit is defined as the perseverance and passion for long-term goals. It involves vigorous efforts in overcoming challenges, with resolute determination over the years despite failure and hardships. Objective: This study determined the level of grit of medical students, its relationship with academic performance, and if there is a difference on the grit level based on their profile. The study also described grit according to various situations, challenges and circumstances. Methods: This was an explanatory sequential mixed method design. Quantitative part used correlation method using the Short Grit Scale. The qualitative part was carried out through open-ended questions and focus group discussion. All students (N=262) enrolled in the School of Medicine were included in the study. Measures of central tendency, t-test, analysis of variance an tests of correlations were utilized to analyze quantitative data. Thematic analysis was used for qualitative data. Results: Findings revealed that medical students are mostly 21-25 years old, female, with familial income of Php 50,000 and above, and mostly Filipinos. Few were transferees and their GWA was satisfactory. The medical students' level of grit was high. There were no significant differences with students' grit regardless of their profile. However, GWA showed a strong relationship with grit (p-value:<0.05). Themes derived from the qualitative data included students' reasons of pursuing medicine, uniqueness as a medical student, their continued survival despite disappointments, their need for time, rest, support and money and reasons for changing medical school. Conclusion: Regardless of the students' profile, a high level of grit is consistently manifested by the medical students. Better academic performance is meaningfully linked to grit. Students who persevere and consistently maintain their efforts will most likely achieve better learning outcomes. Recommendations: Further studies to build grit in medical school are recommended. These include a review of the curriculum to ensure that students can cope with allotted time and course requirements; formation of a support group for students to interact and share sentiments with; initiate collaborative extra-curricular activities to promote and establish a mentoring and support system that will allow teachers, students, and their families to communicate and support each other.
also available, scanned pdf
Thesis (Master of Health Professions Education)--University of the Philippines Manila, July 2018
Panel members: Erlyn A. Sana, PhD, chair/adviser; Melflor A. Atienza, MD MHPEd, reader/critic; Nemuel S. Fajutagana MD MHPEd, member; Ma. Elizabeth M. Grageda PTRP MHPEd, member; Gil P. Soriano RN MHPEd, member
Keywords: Grit